Oral administration of polyamines ameliorates liver ischemia/reperfusion injury and promotes liver regeneration in rats. Issue 9 (22nd July 2016) - Okumura, Shinya; Teratani, Takumi; Fujimoto, Yasuhiro; Zhao, Xiangdong; Tsuruyama, Tatsuaki; Masano, Yuki; Kasahara, Naoya; Iida, Taku; Yagi, Shintaro; Uemura, Tadahiro; Kaido, Toshimi; Uemoto, Shinji
Abstract : Polyamines are essential for cell growth and differentiation. They play important roles in protection from liver damage and promotion of liver regeneration. However, little is known about the effect of oral exogenous polyamine administration on liver damage and regeneration. This study investigated the impact of polyamines (spermidine and spermine) on ischemia/reperfusion injury (IRI) and liver regeneration. We used a rat model in which a 70% hepatectomy after 40 minutes of ischemia was performed to mimic the clinical condition of living donor partial liver transplantation (LT). Male Lewis rats were separated into 2 groups: a polyamine group given polyamines before and after operation as treatment and a vehicle group given distilled water as placebo. The levels of serum aspartate aminotransferase and alanine aminotransferase at 6, 24, and 48 hours after reperfusion were significantly lower in the polyamine group compared with those in the vehicle group. Polyamine treatment reduced the expression of several proinflammatory cytokines and chemokines at 6 hours after reperfusion. Histological analysis showed significantly less necrosis and apoptosis in the polyamine group at 6 hours after reperfusion. Sinusoidal endothelial cells were also well preserved in the polyamine group. In addition, the regeneration of the remnant liver at 24, 48, and 168 hours after reperfusion was significantly accelerated, and the Ki‐67 labeling index and the expressions of proliferating cell nuclear antigen and phosphorylated retinoblastoma protein at 24 hours after reperfusion were significantly higher in the polyamine group compared with those in the vehicle group. In conclusion, perioperative oral polyamine administration attenuates liver IRI and promotes liver regeneration. It might be a new therapeutic option to improve the outcomes of partial LT. Liver Transplantation 22 1231–1244 2016 AASLD